A Morphological Analysis of Inflectional Morphemes in Elon Musk Speech - Ismail Ismail; Wulandari Wulandari; Nurhikmah Nurhikmah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This research aims to investigate types of inflectional morphemes and the most dominant morphemes appearing in Elon Musk Speech. This study is a qualitative research that adopted the data analysis designed by Miles & Huberman (1994) which covers data reduction, data display, and conclusion drawing. The result of this study is that, In particular, For the inflecttional affixes, the affixes that occured were eighty-five (85) suffixes. There were no prefixes. There were seven (7) different types of suffixes, such asa; -s/es indicating plural, -s/es indicating third person singular, -ed indicating past tense, -ed indicating past participle, -‘s indicating possessive, -ing indicating progressive, -est indicating superlative. As a result, suffixes –s/es plural become the mostt dominant suffixed which are being used in Elon Musk’s speech. Since the analysis of this paper is still limited on the inflectional morphemes in Elon Musk’s speech, the other researcher are suggesed to do additional research on Derivational Morphemes using song’s lyric or novel as a different data resources.